Annual reports on NMR spectroscopy. - Webb, G. A. (Graham Alan), 1935- (Annual reports on NMR spectroscopy, 1999)
Over recent years, no other technique has grown to such importance as that of NMR spectroscopy. It is used in all branches of science where precise structural determination is required, and where the nature of interactions and reactions in solution is being studied. Annual Reports on NMR Spectroscopy has established itself as a means for the specialist and non-specialist alike to become familiar with new applications of the technique in all branches of chemistry, including biochemistry, and pharmaceutics. Once again, the Annual Reports on NMR Spectroscopy represents the best work in the field, both in applied and theoretical NMR spectroscopy. The high calibre reports in Volume 38 show the wide biological and physical applications that benefit from this analytical technique.